2002
DOI: 10.1074/jbc.m200521200
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Type of β1,6-N-Acetylglucosaminyltransferase V (GnT-V) Induces Tumor Angiogenesis without Mediation of Glycosylation

Abstract: Angiogenesis is the first regulatory step of tumor progression. Herein, we report on some findings that show that ␤1,6-N-acetylglucosaminyltransferase V (GnT-V) functions as an inducer of angiogenesis that has a novel and completely different function from the original function of glycosyltransferase. A secreted type of GnT-V protein itself promoted angiogenesis in vitro and in vivo at physiological concentrations. The highly basic domain of GnT-V induced the release of fibroblast growth factor-2 from heparan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…FKRP as a molecular chaperone for DG processing and/or targeting, or vice versa, is an intriguing possibility. Whether FKRP activity is required at the sarcolemma for normal muscle function is unclear; however, known glycosyltransferases may possess enzymatic or lectin binding activity at the cell surface (23)(24)(25)30). Overall, our data indicate that FKRP is present at the muscle cell surface, associates with the DGC, and may have a unique role in the ␣DG processing pathway.…”
Section: Discussionmentioning
confidence: 64%
“…FKRP as a molecular chaperone for DG processing and/or targeting, or vice versa, is an intriguing possibility. Whether FKRP activity is required at the sarcolemma for normal muscle function is unclear; however, known glycosyltransferases may possess enzymatic or lectin binding activity at the cell surface (23)(24)(25)30). Overall, our data indicate that FKRP is present at the muscle cell surface, associates with the DGC, and may have a unique role in the ␣DG processing pathway.…”
Section: Discussionmentioning
confidence: 64%
“…N-acetylglucosaminyltransferase V expression is not equal to the expression of b1 -6 branching asparagine-linked oligosaccharides analysed by L 4 -PHA histochemistry (Dosaka-Akita et al, 2004). This is because GnT-V has been shown to function as an inducer of angiogenesis (Saito et al, 2002), which is completely different from the original function of glycosyltransferase, and GnT-V expression does not necessarily result in the synthesis of b1 -6 branching oligosaccharides. Our results showed that GnT-V-expression intensity was well consistent with L 4 -PHA-staining intensity in tumour cells.…”
Section: Discussionmentioning
confidence: 94%
“…1, route 6a). Surprisingly, the secreted form of GnT-V per se is angiogenic, which also promotes metastasis (25) (Fig. 1, route 6b).…”
mentioning
confidence: 99%